Produção da vida urbana e segregação Socioespacial: dinâmicas e desafios pertinentes ao município de Paço do LumiarMaranhão - NUNES, Gisele de Fátima Cardoso (2022)
Dissertation on the ways in which, throughout the socio-historical process of constitution of the urban, certain dimensions of the production and expansion of urban life in capitalist cities are determinants and, at the same time, results of sociospatial segregation. In its formulation, the paper emphasizes relations between capitalist urbanization, housing dynamics, land-real estate interests, urban planning and management, social struggles for the rights to housing and the city, and urban social-spatial segregation in the Brazilian particularity, taking as a concrete base of analysis the municipality of Paço do Lumiar located in the state of Maranhão/Brazil. In the investigation, under the orientation of the historical-dialectical materialism, a method that makes it possible to reconstitute, in terms of thought and analysis, determinations, relations, mediations and contradictions constitutive of historical totalities in which specificities of greater or lesser complexity relevant to the domain of the object of study are defined, bibliographic research was carried out; documentary research, especially of constitutional documents and others related to the field of urban public policies; studies of collections and documents related to the municipality of Paço do Lumiar; interviews with representatives of the government and of residents' political organization movements; direct observation and photographic records of the investigated urban areas. The results of these research and analysis procedures, inserted in the contradictory process of the concrete reality, allow, in the scope of this dissertation, among others a) the demarcation of relations and contradictions between the fundamental social need for housing, the Law, private land tenure regimes and urban state management in contemporary capitalism; b) the reconstitution of characteristics that give content to the specificity of the municipality of Paço do Lumiar, with emphasis on the conditions of its insertion in the Maranhão Island and in the Metropolitan Region of Greater São Luís; c) the configuration of municipal housing and urban dynamics in which popular housing policies, social struggles for the right to housing, growing real estate market, environmental impacts and socio-spatial inequalities are mixed; d) the identification of actions and omissions of the Municipal Public Power in the implementation of urban policies and urbanistic instruments, such as the Municipal Master Plan; e) the verification of processes of mobilization and political organization of dwellers for the 12 right to adequate housing and to the city, expressions of resistance and essential conditions for reversing processes of socio-spatial segregation. Finally, the conclusive notes register the consideration that in the current and unique urban expansion that is verified in Paço do Lumiar, as it is expressed in the region of Vila Epitácio Cafeteira, are related, through a wide range of manifestations, the precariousness of housing, the absence or degradation of services and urban equipment, weaknesses and omissions in the effectiveness of political-legal mechanisms of territorial planning and guarantee of the right to the city provided in the City Statute and the worsening of socio-spatial segregation. It is, therefore, about processes that question the municipal public power, the scholars and the political movements of the urban question field about the terms and the directions of the urban public management in Paço do Lumiar.